Nuevos enfoques de la planificación urbana en Italia - Oliva, Federico (Urban, 2011)
Índice • La anomalía italiana. • La transformación urbana. • La reforma del plan. • La "tensión reformista". • Tres modelos de plan. • La reforma del plan. • La reforma del plan. Resumen El urbanismo italiano se basa en el plan regulador general, PRG, un instrumento rígido y prescriptivo, cimentado en una técnica expropiatoria de imposible aplicación, producto de la ley aún vigente de 1942. En los últimos años, han aparecido instrumentos parciales en el contexto de la desregularización, definidos como programas complejos, con la participación de actores reales y una integración efectiva de recursos públicos y privados. Esta experiencia está siendo sistematizada por la práctica de muchos ayuntamientos y por el Instituto Nacional de Urbanística en su propuesta de nueva legislación, actualmente en discusión en el Parlamento. La propuesta de reforma del PRG se basa, fundamentalmente, en su desdoblamiento en dos instrumentos: el Plan estructural, que define las invariantes a largo plazo, y el Plan operativo, que se refiere a las partes de la ciudad a las que corresponden proyectos de transformación, ligando las intervenciones transformativas a los recursos públicos disponibles. Para terminar el artículo, ejemplifica los experimentos en curso con los casos de varias ciudades a las que agrupa en tres modelos principales. Abstract Italy’s urban planning is based on the general town planning scheme (GTPS), a rigid, prescriptive instrument founded on an expropriatory technique which is impossible to apply, the result of the still-extant Act of 1942. This plan, which has been classed as "a comprehensive, itemised plan", proved efficacious when the principal aim was urban expansion but now needs reforming in order to tackle today’s objective of urban reclassification, the complexity and speed of the processes of urban change, the multiplicity of agents, the onslaught of new demands and the crisis of public resources. Over the last few years partial instruments have appeared within the context of deregulation, defined as complex programmes, with the participation of real agents and the effective integration of public and private resources: for example, the Integrated Intervention Programmes, the Urban Reclassification Programmes or the Urban Recovery Programmes. The experiment is becoming standardised through its being put into practice by many city councils and through the National Institute of Urban Planning including it in its proposal for new legislation currently under debate in Parliament, to be passed in the year 2000. The proposed reform of the GTPS is based mainly on its being split into two instruments: the structural Plan, which defines the aspects not liable to change in the long term, and the operative Plan, which is valid for 5 years and refers to the parts of the city that are eligible for transformation projects, linking the transforming interventions to the public resources available. To conclude, the article gives examples of the experiments in progress with several cities, which it groups together into three main models: structure plan model, urban form model and renewed tradition model.